THE PRODUCTIVE ROLE OF WOMEN IN SEVERAL INDONESIAN FISHING COMMUNITIES - Indrawasih, Ratna (Jurnal Masyarakat dan Budaya, 2015)
Some of the Indonesian women have a role as the family breadwinner. In that case, women have a dual role as a homemaker and a breadwinner (productive role). This phenomenon can also be observed in the fishing communities. As the breadwinner (run productive role), their activities are vary from the pre-production to the post-production. This paper discusses their activities. Data in this paper are gathered both from both the field research as well as secondary one from other researchers. Keywords: Productive Roles, Women, Fishing Communities